2002
DOI: 10.1007/s00418-002-0403-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum-dependent effects of IGF-I and insulin on proliferation and invasion of human first trimester trophoblast cell models

Abstract: Extravillous cytotrophoblasts are specialised epithelial cells of the placenta that proliferate or invade the maternal decidua. Little is known about the mechanisms that regulate these processes. Here the effects of several insulin and insulin-like growth factor-I (IGF-I) doses, either singly or in synergy with serum, on human chorionic gonadotropin-beta (hCG-beta) secretion (RIA), proliferation (cell counting, cyclin B(1) levels) and invasion [Matrigel invasion assay, secretion of matrix metalloproteinases (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…This may indicate a mitogenic effect of insulin on the trophoblast, predominantly at the beginning of pregnancy, whereas fetal insulin will stimulate metabolic processes within the endothelium. In fact, in vitro studies confirmed the mitogenic potency of insulin in trophoblast models (19). This may explain the biphasic growth of the placenta and fetus at around mid-gestation in type 1 and experimental diabetes (20,21).…”
Section: The Insulin Receptormentioning
confidence: 71%
“…This may indicate a mitogenic effect of insulin on the trophoblast, predominantly at the beginning of pregnancy, whereas fetal insulin will stimulate metabolic processes within the endothelium. In fact, in vitro studies confirmed the mitogenic potency of insulin in trophoblast models (19). This may explain the biphasic growth of the placenta and fetus at around mid-gestation in type 1 and experimental diabetes (20,21).…”
Section: The Insulin Receptormentioning
confidence: 71%
“…Glucose uptake by BeWo cells was carried out as described (31) with a few adaptations. At 24,48,72, and 96 h after seeding, the culture media were removed, and cells were washed briefly with tyrode buffer [in mM: 135 NaCl, 5 KCl, 1.8 CaCl 2, 1 MgCl2 (6H2O), and 10 HEPES as described previously (2) with the exception of glucose; the solution was filter sterilized] to remove any residual FBS. Next, the cells were preincubated for 10 min at room temperature in 0.3 ml of warm Tyrode solution to acclimatize with the assay buffer and remove cellular glucose (14).…”
mentioning
confidence: 99%
“…IGF-I facilitates the implantation of the human embryo in the endometrium. Disturbance of IGF-I functions could result in spontaneous miscarriage, preeclampsia, and defects of the embryo (38). It is well known that the incidence of spontaneous miscarriage because of malformations of the fetuses during early pregnancies is much higher in women with poorly controlled diabetes than in nondiabetic pregnancies.…”
Section: Potential Risks Associated With Insulin Analogsmentioning
confidence: 99%